The effect of stress factors on birch Betula pendula Roth - D. Kaňová; E. Kula (Journal of Forest Science, 2004)
In a controlled pot trial, plants of birch (Betula pendula Roth) were treated in six variants: acid watering (pH 3), acid watering with spraying, drought, ammonium sulphate fertilisation, ammonium sulphate fertilisation in combination with drought, and control. The response to the treatment with ammonium sulphate in terms of the increment was discordant as it increased the sensitivity of birch to frost. Drought had a negative effect on increments. A combination of ammonium sulphate and drought; drought; ammonium sulphate and sprayed acid watering delayed the shedding of leaves; this was due to a longer vegetation period, significantly higher nitrogen content in these variants, with the exception of drought.